Nozzle expansion level effect on a suddenly expanded flow - Khan, Sher Afghan; Rathakrishnan, E. (Walter de Gruyter, 2006)
This investigation focuses attention on the effectiveness of active control in the form of micro-jets, located at the base region of a suddenly expanded axi-symmetric ducts, to control the base pressure. The experiments were conducted for Mach numbers 1.25, 1.3, 1.48, 1.6, 1.8, 2.0, 2.5, and 3.0 at NPRs 3, 5, 7, 9, and 11. The area ratios considered were 2.56, 3.24, 4.84, and 6.25. It is found that with increase of NPR the control becomes very effective in increasing the base pressure for all Mach numbers in the range from 1.25 to 2.0. But for higher Mach numbers the control results in decrease of base pressure compared to without control case for Mach number range from 2.5 to 3.0 for NPR 5, 7 and 9. It is found that the micro-jets can serve as active controllers for base pressure. Control effectivness increases for under expanded jets. The wall pressure distribution in the duct was also measured. It is found that the wall pressure distribution is not adversely influenced by the micro-jets.